(untitled) (Journal of Educational Sciences, 2016)
The introduction of information and communication technologies in all processes management of the institution is one of the indicators of innovation component of any university. In order to become an internationally-adaptive innovative university, there must be created an e-university.The article describes the conceptual functional block diagram of the university on the basis of a systematic approach for creating electronic university, as well as the basis of the information model (management, marketing, educational, scientific, economic and business) of e-university. Creating an e-university – a multifunctional approach to information not only of the educational process, but also to all the modules of the university, which are inseparable from each other and the relationship which should ensure the quality of the university as a whole.